Dilated-polyhedron-based DEM analysis of the ice resistance on ship hulls in escort operations in level ice. (November 2021) - Liu, Lu; Ji, Shunying
Abstract: The ice resistance on ships in escort operations in level ice are investigated using the discrete element method (DEM). A dilated polyhedron—generated by the Minkowski sum of a sphere and a polyhedron—is employed in the DEM; this dilated polyhedron-based DEM (DPDEM) is adopted to simulate the ship–ice interaction, wherein the contact force and bond-failure criterion are considered for the collision and fracture of sea ice, respectively. A three-point bending test was simulated with DPDEM, and a field test was conducted in the Bohai Sea to validate the DEM results. Further, a parametric analysis of flexural strength was conducted to identify the parameters involved in the bond-failure criterion. The ice resistance on icebreakers and cargo ships in level ice are simulated using DPDEM. The simulated ice resistances are compared with the Lindqvist and Riska formulas and the model test, which proves the validity of the DEM simulation. The interaction between ships and level ice is simulated parametrically to investigate the ice resistance on cargo ships with and without the icebreaker escort. Influencing factors such as ship speed, ice thickness, and ship breadth were examined to investigate the ice resistance on the escorted cargo ship. Analysis and change rules of the ice resistance on cargos affected by those factors were given. Highlights: DPDEM is developed with the contact model and bond-failure criterion for the breakage simulation of sea ice. Three-point bending tests are simulated to calibrate the parameters. The simulated ice loads on the icebreaker and cargo ship are validated with the Lindqvist and Riska formulas. The reduction rates of the ice load on the cargo ship under escort are analyzed under different conditions.